Social sustainability in development meeting the challenges of the 21st century - Barron, Patrick 1977- (The World Bank, 2023)
All development is about people: the transformative process to equip, link, and enable groups of people to drive change and create something new to benefit society. Development can promote societies where all people can thrive, but the change process can be complex, challenging, and socially contentious. Continued progress toward sustainable development is not guaranteed. The current overlapping crises of COVID-19, climate change, rising levels of conflict, and a global economic slowdown are inflaming long-standing challenges-exacerbating inequality and deep-rooted systemic inequities. Addressing these challenges will require social sustainability in addition to economic and environmental sustainability. Social Sustainability in Development: Meeting the Challenges of the 21st Century seeks to advance the concept of social sustainability and sharpen its analytical foundations. The book emphasizes social sustainability's four key components: social cohesion, inclusion, resilience, and process legitimacy. It posits that -- Social sustainability increases when more people feel part of the development process and believe that they and their descendants will benefit from it. -- Communities and societies that are more socially sustainable are more willing and able to work together to overcome challenges, deliver public goods, and allocate scarce resources in ways perceived to be legitimate and fair so that all people may thrive over time. By identifying interventions that work to promote the components of social sustainability and highlighting the evidence of their links to key development outcomes, this book provides a foundation for using social sustainability to help address the many challenges of our time